2009
DOI: 10.1111/j.1600-6143.2009.02759.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Effects of a Cyclic RGD Peptide in Steatotic Liver Cold Ischemia and Reperfusion Injury

Abstract: The serious need for expanding the donor population has attracted attention to the use of steatotic donor livers in orthotopic liver transplantation (OLT). However, steatotic livers are highly susceptible to hepatic ischemia-reperfusion injury (IRI). Expression of fibronectin (FN) by endothelial cells is an important feature of hepatic response to injury. We report the effect of a cyclic RGD peptide with high affinity for the a 5b 1, the FN integrin receptor, in a rat model of steatotic liver cold ischemia, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…In addition, cyclic RGD at 4 mg/kg BW had been applied in the study of steatotic liver cold ischemia and reperfusion injury [30]. We also performed a pilot study at a dose of 10 mg/kg BW cRGD, but did not observe a noticeable difference in comparison with the 5 mg/kg BW dose.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, cyclic RGD at 4 mg/kg BW had been applied in the study of steatotic liver cold ischemia and reperfusion injury [30]. We also performed a pilot study at a dose of 10 mg/kg BW cRGD, but did not observe a noticeable difference in comparison with the 5 mg/kg BW dose.…”
Section: Discussionmentioning
confidence: 96%
“…We conclude that the mechanism used by sesamol to reduce tissue injury is inhibiting the recruitment of inflammatory cells as well as inhibiting the expression and activity of MMP-9, thereby attenuating the breakdown of the cytoskeleton proteins of hepatocytes after the onset of SOS. During SOS, sinusoidal endothelial cells [9] and recruited inflammatory cells [6,[14][15][16] become inflamed and release active MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…Monocrotaline-induced SOS is characterized by elevated levels of aspartate transaminase (AST), alanine transaminase (ALT), and hepatic injury with steatosis [4], recruitment of mast cells [5], CD 68 ? Kupffer cells [6], neutrophils [7], myeloperoxidase (MPO) activity [8], matrix metalloproteinase-9 (MMP-9) activity and expression [9], and decreased tissue inhibitor of matrix metalloproteinase-1 (TIMP-1) expression [10,11]. The late phase (48 h) of SOS is characterized by the recruitment of inflammatory cells that release active MMP-9 [6,[12][13][14][15][16], which ultimately breaks the extracellular matrix proteins laminin and collagen in rats [9,17].…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of evidence supporting the view that cell attachment to ECM proteins and subsequent degradation are related events. Indeed, studies from our laboratory have shown that fibronectin interactions with its two α4β1 and α5β1 integrin receptors, expressed on leukocytes, are capable of regulating MMP-9 expression by leukocytes in hepatic IRI [68;101*]. Others have demonstrated that MMP-9 activation involves nitric oxide (NO)-mediated metalloproteinase S-nitrosylation S [86].…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%